2021
DOI: 10.1016/j.ebiom.2021.103220
|View full text |Cite|
|
Sign up to set email alerts
|

A chemical genetic screen identifies Aurora kinases as a therapeutic target in EGFR T790M negative, gefitinib-resistant head and neck squamous cell carcinoma (HNSCC)

Abstract: Background: Overexpression of epidermal growth factor receptor (EGFR), and downstream pathway activation appears to be a common oncogenic driver in the majority of head and neck squamous cell cancers (HNSCCs); yet targeting EGFR for the treatment of HNSCC has met with limited success. Apart from the anti-EGFR antibody cetuximab, no small molecule EGFR/tyrosine kinase inhibitors (TKIs) have progressed to routine clinical use. The aim of this study was to determine factors contributing to the lack of response to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 42 publications
0
8
0
Order By: Relevance
“…TAK-901 is an Aurora kinase inhibitor. Aurora kinases have recently been identified as therapeutic targets in EGFRnegative, gefitinib-resistant HNSCC cell lines (44). Intriguingly, Aurora kinase A (AURKA) has been shown to limit PI3Kpathway inhibition in a breast cancer model suggesting a dependent signaling network (45).…”
Section: Discussionmentioning
confidence: 99%
“…TAK-901 is an Aurora kinase inhibitor. Aurora kinases have recently been identified as therapeutic targets in EGFRnegative, gefitinib-resistant HNSCC cell lines (44). Intriguingly, Aurora kinase A (AURKA) has been shown to limit PI3Kpathway inhibition in a breast cancer model suggesting a dependent signaling network (45).…”
Section: Discussionmentioning
confidence: 99%
“…4B), thereby contributing to ability of these tumors to survive treatment with EGFR inhibitors; this study showed that AURKA inhibitors synergize with EGFR inhibitors to eliminate EGFR-resistant cells in vitro and in vivo. 99 Aurora inhibitors have been identified as cytotoxic in patient-derived HNSCC cell lines that were both sensitive and resistant to the EGFR inhibitor gefitinib; in this study, resistant cells had wild-type EGFR with increased levels of phosphorylated AURKA 130 . Such results suggest means to apply AURKA inhibitors in combination therapies, as discussed below.…”
Section: Cancer-promoting Function Of Overexpressed Aurkamentioning
confidence: 64%
“…Rather than impacting the metastatic process, it is possible that this vulnerability reflects a generalized reduction in cell cycling that occurs during EMT with a concomitant sensitivity to all cell cycle inhibitors. We recently demonstrated the same phenomenon during drug resistance: reduction in cell proliferation, limited AURK expression and sensitivity to inhibitors of AURK and other cell cycle targets 41 . Nevertheless, the ability to profile tumors and identify vulnerabilities in metastasis-inducing clones is an attractive notion, with increasing interest in low-dose, long term anti-metastatic therapy.…”
Section: Discussionmentioning
confidence: 82%